A New Class of Lasing Materials: Intrinsic Stimulated Emission from Nonlinear Optically Active Metal–Organic Frameworks. Issue 17 (20th February 2017) - Medishetty, Raghavender; Nalla, Venkatram; Nemec, Lydia; Henke, Sebastian; Mayer, David; Sun, Handong; Reuter, Karsten; Fischer, Roland A.
Abstract : Blue‐color stimulated emission with low threshold power is observed from In‐ and Zn‐MOFs, which feature a highly fluorescent chromophore densely packed and rigidly linked to the metal‐ion centers in the solid state. The density‐of‐states and transition dipole moments are calculated and the stimulated emission phenomenon is correlated with these properties.